Structure of a sheet-laccolith system revealing the interplay between tectonic and magma stresses at Stardalur Volcano, Iceland - Pasquare, F; TIBALDI, ALESSANDRO (Journal of Volcanology and Geothermal Research, 2007)
This paper provides detailed structural data on the faults and intrusions of the eroded Stardalur volcano, in the Esja peninsula at the SW margin of the Icelandic rift, and new lithostratigraphic data on the host rocks. A swarm of centrally-dipping sheets, emplaced with a fan-shaped geometry in section view, depicts an ellipse in plan view with an about E-W major axis. Sheet intensity reaches 80% in one 100-m transect near the central portion of the swarm, where sheets strike E-W with sub-vertical dip. A 200-m-thick, multiply-intrusive body forms a laccolith in the middle of the centrally-dipping sheet swarm, at a higher altitude. Individual intrusive units within this laccolith are sub-vertical and strike E-W in the center, acquiring a sill-like geometry outwards, and were emplaced in a stress field locally dominated by a N-S-directed least principal stress (sigma 3). Within the inclined sheet swarm, the stress tensor rotated in response to an excess magma pressure, probably linked to an underlying magma chamber, which interacted with the tectonic stresses. Crosscutting relationships between the various intrusions and with the host rock indicate that the activity in the central zone of the Stardalur volcano ended with the emplacement of the laccolith. Later eruptions, if they occurred at all, were fed by centrally-dipping sheets. In the final stage, NNE-striking regional vertical dykes and normal faults cut the previous structures in response to dominant regional plate tectonic stresses with a WNW-ESE directed sigma 3 and a NNE-SSW directed intermediate principal stress (sigma 2). (c) 2006 Elsevier B.V. All rights reserved.